Enhancing customer behavior and gratitude towards the use of social commerce in Malaysia - Ng, Alex Hou Hong; Wider, Walton; Ho, Ree Chan; Wong, Chee Hoo; Ngui, Kwang Sing (Asian Development Policy Review, 2024)
This study aims to examine the extent to which customers feel grateful towards social commerce, focusing on the satisfaction they derive from it. It also explores how social commerce has the potential to significantly change the way people shop online, particularly in a dynamic and interactive network setting. A conceptual framework was created to identify the specific gratifications that customers seek in social commerce, using the uses and gratification theory. The study utilized structured equation modeling to analyze data obtained from 262 social commerce customers in Malaysia via a questionnaire. The analysis demonstrated that convenience, hedonic value, and social influence play a crucial role in increasing customer gratitude towards social commerce. The assessment of customer acceptance and satisfaction with the implementation of social media technology in online retail heavily relies on these key factors. With a focus on the effects of social media features and functionalities, the paper offers a theoretical understanding of how use and gratification aspects affect shopping in social commerce. It indicates that social commerce is not just a choice but an essential component of the business ecosystem, requiring companies to invest in order to meet customer expectations and promote successful interaction.